PERGESERAN STRUKTUR KALIMAT DEKLARATIF DALAM TERJEMAHAN ILOKUSI BAHASA INGGRIS KE DALAM BAHASA INDONESIA DALAM NOVEL “FAMILY ALBUM” DAN “ALBUM KELUARGA” - I Gusti Ayu Agung Dian Susanthi (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2014)
ABSTRACT This research delas with the analysis of skewing in translating English illocutionary force into Indonesian in the novel entitled ‘Family Album’ by Steel (1989) and ‘Album Keluarga’ by Prajoko (2005). It aims at identifying the condition of translation which refers to the process of translation in terms of skewing. It also aims at discovering how such instances of skewing in terms of illocutionary force are translated into Indonesian. Besides, the equivalence of the translation is also discussed in this thesis. The theories applied in this study are mainly based on the theories proposed by some experts in the field of semantic and translation studies; namely the concept of Skewing proposed by Larson (1998) and to support the study, other theories are also used; there are speech act theory by Searle (1979), the theory of equivalence proposed by Nida (1974). The data were taken from a novel entitled ‘Family Album’ by Steel (1989) and its translation ‘Album Keluarga’ by Prajoko (2005). The data of this study were obtained by observation and then the data were classified into classification problems. The collected data were organized into categories of skewing in terms of illocutionary force then analyzing the process of translating the English illocutionary force into the target language. The data were descriptively analyzed based on the theories applied in this study. There are some expression found in the SL which are used rhetorically. They are used to convey various functions or meanings, such as: Declarative sentence conveys advice (skewing from declarative grammatical form of illocutionary force to imperative); Declarative sentence conveys distrust (skewing from declarative grammatical form of illocutionary force into interrogative). Keywords: skewing, illocutionary Force, The Process of Translation